COMPARSION OF EFFECTIVENESS OF LOW-DOSE INTRAVENOUS KETAMINE (0.2 MG/KG) WITH (0.5 MG/KG) INTRAVENOUS TRAMADOL FOR THE PREVENTION OF POST- SPINAL ANESTHESIA SHIVERING (The Research of Medical Science Review, 2025)
OBJECTIVE: To differentiate between the efficacy of intravenous ketamine 0.2 mg/kg) and 0.5 mg/kg) intravenous tramadol using minimum dosage as remedy for the prevention of post-operative shivering due to anesthesia. STUDY SETTING: Department of Anesthesia NWGH Peshawar. STUDY DESIGN: Randomized controlled trial STUDY DURATION: 7 th November 2021 to 7 th May 2022. MATERIAL AND METHODS: A total of 188 94 in each group) patients were added to the study using non probability consecutive sampling technique. RESULTS: Distribution of Age among groups of 188 94 in each group) were analyzed as n= Among group A ketamine 0.2 mg/kg) the age category 20- 30 Years) was 842.1%) and in group B 0.5 mg/kg) intravenous tramadol ) was 1157.9%) The age category 31-40 years) group A ketamine 0.2 mg/kg)was 646.2%) and group B 753.8%)The age category 41-50 Years) group A ketamine 0.2 mg/kg)was 750.0%)and group B 0.5 mg/kg) intravenous tramadol ) was 750.0%) The age category 51-60 Years) group A ketamine 0.2 mg/kg)was 964.3%) and group B 0.5 mg/kg) intravenous tramadol ) was 535.7% Mean age was 51.56 years with standard deviation ±3.357 Distribution of gender among the groups of 188 94 in each group) were analyzed as n= Among group A ketamine 0.2 mg/kg) Male was 1961.3%) and group B 0.5 mg/kg) intravenous tramadol ) Male was 1238.7%) Among Group A ketamine 0.2 mg/kg) Female was 1137.9%) and group B 0.5 mg/kg) intravenous tramadol ) Female was 1862.1%) CONCLUSION: Therefore, in accordance with our findings, we have come to the conclusion that tramadol is safe and effective in managing shivering in patients who have had spinal anesthesia. Another advantage is its maintenance of a hemodynamically stable profile.